2020
DOI: 10.1002/ejoc.201901694
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic Routes to Natural Isocyanides

Abstract: As intriguing as it may appear, natural products bearing an isocyanide function are well known in different kingdoms of living organisms. An important question in terms of biochemistry is, of course, the origin of such a functional group and the mechanisms that have evolved in biosynthetic pathways to afford the formation of isocyanides. The latest studies dedicated to such endeavours are analysed therein in view of the producing organism metabolisms (e.g. micro‐organisms, marine invertebrates). The in‐situ re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 103 publications
0
26
0
Order By: Relevance
“…The biosynthesis of isonitrile groups by enzymes is unusual, but several have been reported that catalyse the reaction efficiently [37][38][39][40][41][42][43][44]. Most of those enzymes are flavindependent; however, recently, a nonheme iron dioxygenase was identified that biosynthesized an isonitrile group from R-3-((carboxymethyl)amino)butanoic acid through an oxidative decarboxylation reaction [43].…”
Section: Introductionmentioning
confidence: 99%
“…The biosynthesis of isonitrile groups by enzymes is unusual, but several have been reported that catalyse the reaction efficiently [37][38][39][40][41][42][43][44]. Most of those enzymes are flavindependent; however, recently, a nonheme iron dioxygenase was identified that biosynthesized an isonitrile group from R-3-((carboxymethyl)amino)butanoic acid through an oxidative decarboxylation reaction [43].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, a methyl ketone was evidenced by a key HMBC correlation from the methyl H 3 -12 (δ H 2.28, s) to C-10 and C-11 (δ C 200.1). The large 3 J-coupling constant value of 16 Hz between H-9 and H-10 confirmed the E configuration of the double bond. In this case, no Cotton effect was observed in the ECD spectrum of 5, suggesting bubaridin E (5) to be a racemic mixture.…”
Section: Resultsmentioning
confidence: 60%
“…15 These metabolites possess a terpene scaffold bearing a nitrogen-containing functional group, the most common being isocyanide (-NC), isocyanate (-NCO), isothiocyanate (-NCS) or formamide (-NH-CHO), but also dichloroimine, carbamate, urea or amine. 16 This growing class of metabolites (over 300 to date) includes mainly sesquiterpenoids and diterpenoids that contain one or up to three nitrogenous functions around a variety of terpene skeletons. In the case of the Bubarida sponge studied here, all new compounds possess the same bisabolene skeleton characterised by a 3,6-methylalkyl disubstituted cyclohexane ring and a nitrogen always substituted at the position C-3 (mainly formamide).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the isonitrile group is not found in mammals and vertebrates, the evolution of specific biosynthetic pathways has ensured their presence in many terrestrial and marine natural compounds. 4 The reactivity of isonitriles as weak nucleophiles is limited to highly electrophilic species such as resonance-stabilized carbocations, iminium, N -alkylquinolinium, and tropylium ions, which are often accompanied by a second nucleophile for a double α-addition. 5 Thus, isonitriles are mostly unreactive in the presence of biologically occurring functional groups such as alcohols, amines, thiols, carboxylic acids, aldehydes, and ketones.…”
Section: Isonitriles: the Smallest Bioorthogonal Functional Groupsmentioning
confidence: 99%